2016
DOI: 10.3389/fphar.2016.00389
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Prevents Aβ1-42-Induced Toxicity via a Paracrine Signaling Mediated by Transforming-Growth-Factor-β1

Abstract: Selective reuptake inhibitors (SSRIs), such as fluoxetine and sertraline, increase circulating Transforming-Growth-Factor-β1 (TGF-β1) levels in depressed patients, and are currently studied for their neuroprotective properties in Alzheimer’s disease. TGF-β1 is an anti-inflammatory cytokine that exerts neuroprotective effects against β-amyloid (Aβ)-induced neurodegeneration. In the present work, the SSRI, fluoxetine, was tested for the ability to protect cortical neurons against 1 μM oligomeric Aβ1-42-induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 66 publications
0
51
0
Order By: Relevance
“…Indeed, there are some reports of tau-induced cell cycle entry in neurons (Andorfer et al, 2005;Bonda et al, 2009;Jaworski et al, 2009;Seward et al, 2013a;Hradek et al, 2014), albeit entry mediated by NFT has been contested (Jaworski et al, 2009), and at least in some cases it involves Aβ (Seward et al, 2013a;Hradek et al, 2014). When compared to tau-related models, cell cycle deregulation has been vigorously researched in models of Aβ pathology (Copani et al, 1999(Copani et al, , 2006Giovanni et al, 1999Giovanni et al, , 2000Park et al, 2000;Wu et al, 2000;Kruman et al, 2004;Sortino et al, 2004;Yang et al, 2006;Caraci et al, 2008;Majd et al, 2008;Varvel et al, 2008Varvel et al, , 2009Bhaskar et al, 2009;Lopes et al, 2009Lopes et al, , 2010Li et al, 2011;Modi et al, 2012Modi et al, , 2015Seward et al, 2013b;Hradek et al, 2014;Merlo et al, 2015;Caraci et al, 2016;Leggio et al, 2016; Table 1). Virtually all reports report cell cycle related cell death, which is of relevance for senescence.…”
Section: Neuronal Cell Cycle Entry In Admentioning
confidence: 99%
“…Indeed, there are some reports of tau-induced cell cycle entry in neurons (Andorfer et al, 2005;Bonda et al, 2009;Jaworski et al, 2009;Seward et al, 2013a;Hradek et al, 2014), albeit entry mediated by NFT has been contested (Jaworski et al, 2009), and at least in some cases it involves Aβ (Seward et al, 2013a;Hradek et al, 2014). When compared to tau-related models, cell cycle deregulation has been vigorously researched in models of Aβ pathology (Copani et al, 1999(Copani et al, , 2006Giovanni et al, 1999Giovanni et al, , 2000Park et al, 2000;Wu et al, 2000;Kruman et al, 2004;Sortino et al, 2004;Yang et al, 2006;Caraci et al, 2008;Majd et al, 2008;Varvel et al, 2008Varvel et al, , 2009Bhaskar et al, 2009;Lopes et al, 2009Lopes et al, , 2010Li et al, 2011;Modi et al, 2012Modi et al, , 2015Seward et al, 2013b;Hradek et al, 2014;Merlo et al, 2015;Caraci et al, 2016;Leggio et al, 2016; Table 1). Virtually all reports report cell cycle related cell death, which is of relevance for senescence.…”
Section: Neuronal Cell Cycle Entry In Admentioning
confidence: 99%
“…Interestingly different preclinical and clinical studies have shown that ketamine is endowed with anti-inflammatory activity (De Kock et al, 2013) and reverses inflammation-induced depression in the lipopolysaccharide model by decreasing brain levels of inflammatory cytokines (Yang et al, 2013) or by blocking the effects of quinolinic acid, a downstream product of the kynurenine pathway, on NMDA receptors (Walker et al, 2013b). Furthermore, recent in vitro studies have shown that fluoxetine and venlafaxine increase the release of TGF-b1, an antiinflammatory cytokine that is reduced in nonresponder MDD patients (Vollmar et al, 2008;Caraci et al, 2016).…”
Section: E Immune System Dysregulation and Neuroinflammationmentioning
confidence: 99%
“…Fluoxetine effectively acts on a wide spectrum of mood disorders and protects against the adverse effects of different types of stressors by decreasing some effects of stress on the immune system and by protecting against oxidative damage. Different molecular mechanisms have been proposed to explain its neuroprotective effects, including BDNF (Brain-derived Neurotrophic Factor) release, antagonism on NMDA (N-methyl-D-aspartate) receptors, the inhibition of NF-kB (Nuclear Factor Kappa B Subunit 1) activity, and inhibition of the release of pro-inflammatory factors (TNF-α, Tumor Necrosis Factor-Alpha, IL-1β, Interleukin 1 Beta) from microglial cells [12]. However, the underlying mechanisms of its therapeutic efficacy remain unclear, particularly those related to its antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%